Perancangan Aplikasi Sosialisasi Penerimaan Anggota Polri Berbasis Web Pada Polda Aceh - Agnes; Mukhtar; Taufiq Iqbal (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
One of the challenges in the recruitment process for members of the Indonesian National Police (Polri) is the persistent rumors that candidates need to pay large sums of money to pass the selection, despite the official policy stating that the process is free of charge. This study aims to design a web-based application to disseminate accurate information about the recruitment process at Polda Aceh, with the goal of eliminating misconceptions and increasing public participation. The application integrates multimedia elements, including animations, videos, and images, to enhance public engagement. The development methodology combines the Waterfall model and Agile approach, allowing flexibility in incorporating user feedback and making improvements during the development process. The application was developed using HTML, CSS, PHP, and MySQL, enabling the recruitment information to be accessed via mobile devices or websites. The system also accelerates report generation and delivers comprehensive content such as socialization materials, videos, and animations, which are essential in motivating prospective applicants.